SPEECH ACT ANALYSIS ON THE MAIN CHARACTER’S UTTERANCE IN UP MOVIE - Syahril Dian Ismani (Universitas Negeri Gorontalo, 2022)
This research focused on directive speech acts in main character’s utterance in UP movie. the problems of this research are: what types of directive illocutionary acts are applied in UP movie, which type is mostly dominant in the main character’s utterance in UP movie. meanwhile, the objectives of the research are: to identify the type of directive illocutionary acts in main character’s utterance in UP movie, to identify mostly dominant in main character’s utterance in UP movie. the researcher used theory by Searle (1979) to analyze the data. This research used a qualitative method. The researcher found 93 data type of directive speech act from main character’s utterance in UP movie, there are: (35) ask, (11) request, (24) order, (7) forbid, (11) suggest, and (5) warn. Conclusion, the most dominant types that uttered in this research is ask type.